Hashimoto’s thyroiditis in an Egyptian cohort: clinical, functional, and ultrasonographic features with insights into nodule risk - El Aghoury, Aliaa; Abd ElHafeez, Samar; El Sabaa, Basma; Abo El Wafa, Reham; Abo El Wafa, Waleed; El Naggar, Hanaa; Ibrahim, Eiman; Naguib, Rania; Bondok, Maha (Frontiers in Endocrinology, 2025)
Background/aimHashimoto’s thyroiditis (HT) is a highly prevalent autoimmune disorder. Its coexistence with benign and malignant thyroid nodules is well-documented; however, data from non-Western countries remain limited. Our objectives were to determine the demographics, clinical presentation, biochemical parameters, and thyroid ultrasonographic findings in an Egyptian cohort with HT; estimate nodule prevalence; and identify potential risk factors for nodular presentation.Patients and methodsA cross-sectional study was conducted on 408 newly diagnosed patients with HT at Alexandria University Hospital. Sociodemographic, clinical presentation, biochemical (thyroid function and autoantibodies thyroperoxidase and thyroglobulin Abs), and ultrasonographic data were collected. Thyroid nodules were classified according to the American College of Radiology Thyroid Imaging Reporting and Data System (ACR TI-RADS). Fine-needle aspiration cytology (FNAC) was classified by the Bethesda system (BSRTC). Multiple logistic regression identified predictors of nodularity.ResultsAmong our cohort of 408 participants (female-to-male ratio of 15:1; mean age 38.6 years), 23.5% had thyroid nodules on ultrasound. Nodules were more frequent in those ≥35 years and with a family history of thyroid disease. Compressive symptoms were more common in the nodular group (33.0% vs. 18.6%). Hypothyroidism was observed in 80.9%, predominantly subclinical, and was more frequent in the non-nodular group (80.4% vs. 71.1%). Autoantibodies tested positive in 87.5%. One-third had diffuse enlargement; most nodules were classified as TIRADS 3 or 4. FNAC (n = 49) showed 63.2% benign, 32.7% indeterminate, and 4.1% non-diagnostic. Histopathology (n = 18) identified papillary thyroid cancer in 44.4%. In multiple logistic regression, age 35–50 (OR = 7.023, 95% CI: 1.447–334.090), age ≥50 (OR = 8.589, 95% CI: 1.740–42.402), family history of goiter/thyroid cancer (OR = 5.177, 95% CI: 1.055–25.403), lower TSH (OR = 0.981, 95% CI: 0.966–0.997), TPOAb (OR = 0.998, 95% CI: 0.997–0.999), and larger thyroid volume (OR = 1.036, 95% CI: 1.012–1.060) were independent predictors of nodularity.ConclusionHT shows heterogeneous clinical presentations, with subclinical hypothyroidism predominating. Compressive symptoms are more common in patients with nodules. Ultrasound and FNAC are essential for the management of nodules with HT and can help prevent unnecessary surgery. Older age, larger thyroid volume, and a positive familial history of goiter and/or thyroid cancer are major predictors for nodularity. The malignancy rate is ~2%, with microcalcifications strongly associated with malignancy.